Books of the Month: The Cambridge History of Christianity - Foster, Paul (The expository times, 2007)
The article offers information on several volumes of the book "Cambridge History of Christianity" published by Cambridge University Press. The first volume covers pre-Constantinian Christianity. The history of Christianity from 1815 to 1914 is covered in the volume eight titled "World Christianities." It also provides an overview of the opening chapter of the volume on "Eastern Christianity" which is about the Byzantine Commonwealth.